Vulnerability, Crises and Debt Maturity: Do IMF Interventions Increase Reliance on Short‐Term Debt?1. (December 2013) - Saravia, Diego
Abstract It has been widely argued that excessive short‐term debt has been a major cause of recent financial crises. I find evidence that IMF lending programmes on average serve to reduce the maturity of sovereign bond issues, which is an undesirable effect. However, the impact of IMF interventions varies, importantly, across countries which differ according to measures of their fundamental macroeconomic soundness: countries with weak fundamentals tend to lengthen their debt maturities following on the heels of an IMF lending programme. This suggests that the IMF should focus particularly on ensuring that its interventions do not increase incentives for short‐term debt issuance in countries not at risk of imminent crisis, but which might put themselves at risk through imprudent borrowing practices.